2015
DOI: 10.3382/ps/peu046
|View full text |Cite
|
Sign up to set email alerts
|

II. Evaluation of the impact of alternative light technology on male broiler chicken stress

Abstract: This study evaluates the impact of light-emitting diodes (LEDs), cold cathode fluorescent lamps (CCFLs), and incandescent lamps on broiler welfare in response to recent interest in the agriculture industry to transition to more energy-efficient lighting technologies. Male Ross 708 broilers (n=672) were raised to 6 wk age in 8 light-tight modified large colony houses under identical intermittent lighting conditions using 4 unique types of lamps, which were gradually dimmed throughout the study. Incandescent lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
0
12
0
6
Order By: Relevance
“…These findings disagree with those reported by De Marco et al (2013) who found in BP a mean value of 0.40 ± 0.02; probably this can be due to the older age of tested animals. A part from the breed the H:L parameter can be affected by a variety of factors including sex, and age of birds (Rogers et al 2015). Bayyari et al (1997) reported that lymphocyte numbers were lower in a line of turkeys selected for heavier BW than in a line selected for increased egg production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings disagree with those reported by De Marco et al (2013) who found in BP a mean value of 0.40 ± 0.02; probably this can be due to the older age of tested animals. A part from the breed the H:L parameter can be affected by a variety of factors including sex, and age of birds (Rogers et al 2015). Bayyari et al (1997) reported that lymphocyte numbers were lower in a line of turkeys selected for heavier BW than in a line selected for increased egg production.…”
Section: Resultsmentioning
confidence: 99%
“…For that reason these topics have received much attention in the poultry industry in recent years due to the growing concerns for welfare. Heterophil to lymphocyte (H/L) ratio and plasma corticosterone concentration are widely used as stress evaluation criterion in poultry (Debut et al 2005;Franciosini et al 2005;Cirule et al 2012) and are well known as physiological indicators of welfare (Rogers et al 2015;Alm et al 2016). The H/L ratio is a more reliable indicator of mild to moderate stress than plasma corticosterone (Maxwell 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Stres sebelum pemotongan memengaruhi sistem metabolisme ayam menjadi lebih cepat, sehingga memerlukan suplai oksigen yang banyak (Rogers et al, 2015). Jika ketersediaan oksigen sedikit, akan dapat menurunkan kadar hemoglobin (Scanes, 2016).…”
Section: Pendahuluanunclassified
“…A iluminação pode influenciar no crescimento e características de carcaça para frangos de corte (Olanrewaju et al, 2016a,b;Purswell et al, 2018;Rogers et al, 2015a), respostas fisiológicas (Olanrewaju et al, 2015;Rogers et al, 2015b) e também o comportamento e o bem-estar no sistema de produção (Rogers et al, 2015b). A qualidade, intensidade, fotoperíodo e cor da luz interferem no comportamento e desenvolvimento das aves (Mendes et al, 2010;Benson et al, 2013).…”
Section: Aspectos Gerais Da Influência Da Iluminação No Desempenho E unclassified
“…A visão das aves é mais sensível que a humana, possuem sensibilidade entre o comprimento de onda de 475 e 650 nm (Bowmaker et al, 1997;Prescott & Wathes 1999;Purswell et al, 2018). A visão é o sentido que mais influencia no comportamento das aves (Rogers et al, 2015b;Rault et al, 2016). A alta ou baixa intensidade de luz no período de alojamento pode influenciar, positivamente ou negativamente, no comportamento das aves, comprometendo o bem-estar e consequentemente a eficiência da produção (Mendes et al, 2010;2013;Rault et al, 2016;Purswell et al, 2018).…”
Section: Aspectos Gerais Da Influência Da Iluminação No Desempenho E unclassified